Remanufacturing of functional surfaces using developed ECH machine - Harpreet Singh; Pramod Kumar Jain (Journal of Remanufacturing, 2016)
Determination of optimal input parameters is one of the important elements in any process planning of the metal parts. The aim of the study is to investigate the optimization of processing parameters in order to enhance the surface micro-finish and geometrical accuracy of the recovered functional surfaces made of SS316 material using a newly developed electrochemical honing (ECH) machine. ECH is a prominent hybrid machining process, which is widely used for precision finishing of intricate shapes and hard materials with an efficient and effective manner. In this work, discarded functional surface of the cylindrical shafts is recovered using twin wire arc (TWA) technique and its surface topography was studied using developed micro-finish machine. The results show that the ECH of recovered surfaces gives a glazed texture and produce an average surface roughness of 0.347 μm with the processing time of 90 s. The monitored outputs such as surface roughness (average, Ra and maximum, Rt) and geometrical accuracy such as out-of-roundness (OR) was measured during the investigation to optimized the process performance characteristics.
Keywords: 650; Electrochemical honing (ECH); Cylindrical shafts; SS316; Surface roughness; Out-of-roundness